A Unified Treatment of the Relationship Between Ligand Substituents and Spin State in a Family of Iron(II) Complexes. (1st March 2016) - Kershaw Cook, Laurence J.; Kulmaczewski, Rafal; Mohammed, Rufeida; Dudley, Stephen; Barrett, Simon A.; Little, Marc A.; Deeth, Robert J.; Halcrow, Malcolm A.
Abstract: The influence of ligands on the spin state of a metal ion is of central importance for bioinorganic chemistry, and the production of base‐metal catalysts for synthesis applications. Complexes derived from [Fe(bpp)2 ] 2+ (bpp=2, 6‐dipyrazol‐1‐ylpyridine) can be high‐spin, low‐spin, or spin‐crossover (SCO) active depending on the ligand substituents. Plots of the SCO midpoint temperature ( T 1 / 2 ) in solution vs. the relevant Hammett parameter show that the low‐spin state of the complex is stabilized by electron‐withdrawing pyridyl ("X") substituents, but also by electron‐donating pyrazolyl ("Y") substituents. Moreover, when a subset of complexes with halogeno X or Y substituents is considered, the two sets of compounds instead show identical trends of a small reduction in T 1 / 2 for increasing substituent electronegativity. DFT calculations reproduce these disparate trends, which arise from competing influences of pyridyl and pyrazolyl ligand substituents on Fe‐L σ and π bonding.